PENGARUH GAJI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS TENAGA HONORER PADA SATUAN POLISI PAMONG PRAJA KOTA BENGKULU - Muhamad Galy Njoman Ari Pribowo; Deni Septadinata (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
Organization wants employees in its company to havegood work loyalty so that organizational goals can be achieved by good. This study aims to determine and examine the effect of salary, work environment, on the loyaltyof the Bengkulu City Satpol PP Honorary Personnel. This type of research is a quantitativeapproach. The method used in this research is descriptive method. The population in this studywere all Honorary Personnel of the Civil Service Police Unit of Bengkulu City with a total of 246employees.the sample amounted to 71 people. Based on the results of the study Salary has apositive and significant effect on the Loyalty of Honorary Personnel in the Bengkulu City CivilService Police Unit. It is proven in the results of the t-test more than ttable (3,652» 1.995) with asignificance of 0.00 « 0.05. The work environment has a positive and significant effect on theLoyalty of Honorary Personnel in the Bengkulu City Civil Service Police Unit. The t-count for thevariable Salary (X1) is 3.652, this means that t-count is more than t-table (3.652 »1.995) with asignificance of 0.00 « 0.05.